RC48-ADC combined with tislelizumab as neoadjuvant treatment in patients with HER2-positive locally advanced muscle-invasive urothelial bladder cancer: a multi-center phase Ib/II study (HOPE-03) - Wen, Feng; Lin, Tianhai; Zhang, Peng; Shen, Yali (Frontiers in Oncology, 2024)
Background: Bladder cancer with Human Epidermal Growth Factor Receptor 2 (HER2) high expression is related to pathological malignancy and poor prognosis. The standard care for muscle-invasive urothelial bladder cancer (MIBC) is neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC) with pelvic lymph node dissection. For HER2 positive MIBC, the efficacy of cisplatin-based NAC is unsatisfied, and adverse reactions are inevitable or even intolerable. New regimens with higher efficiency and lower toxicity are needed to be explored in the neoadjuvant setting for this population.Methods: HOPE-03 is a multi-center, open-label, single-arm, phase Ib/II study, aiming to evaluate the safety and efficacy of RC48-ADC (Distamab Vedotin, DV), a humanized anti-HER2 antibody conjugated with monomethyl auristatin E, and tislelizumab (PD-1 antibody) as a novel neoadjuvant treatment combination in patients with HER2 positive locally advanced urothelial MIBC. Fifty-one patients with cT2-4bN0-3M0-1a pathological and imaging diagnosed HER2 positive (Immunohistochemistry status 3+ or 2+ or 1+) MIBC will be recruited. Of them, 6 patients are enrolled in the dose-escalation phase (3 patients in RC48-ADC 1.5 mg/kg group and 3 patients in 2.0mg/kg group), and 45 patients enter into phase II study (the expected recommended phase II dose for RC48-ADC is 2.0mg/kg). Patients without disease progression will receive radical cystectomy or bladder-sparing therapies as their will after neoadjuvant treatment. The primary endpoints are clinical complete remission rate (cCR, T0/Ta/Tis), pathological complete remission rate (pCR) and safety. The secondary endpoints are overall survival (OS), local recurrence free survival (LRFS), distant metastasis free survival (DMFS) and quality of life.Discussion: HOPE-03 trial will give a description about the safety profile of RC-48 and tislelizumab combination in the neoadjuvant treatment of HER2 positive locally advanced urothelial MIBC, and the efficacy will be explored as well in this population.